PENGARUH SENAM ERGONOMIK TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA SUMBER AGUNG KECAMATAN JATIREJO KABUPATEN MOJOKERTO - Triwibowo, Heri; Frilasari, Heni; Hapsari, Yustika Widya (S1 Keperawatan, 2015)
Hypertension is a very common illness found in the society. Not only decreases quality of life, it also threatens the patients life. Hyertension known as heterogeneous group of diseasebecause it can attack anyone from any range of age and economy class. There are two therapies for hypertension namely farmacology and nonfarmacology. One of non farmacology therapy is by doing ergonomic exercises. The aim of the research is to find out the impact of ergonomic exercises on blood pressure of hypertension patients in SumberAgung Village JatirejoSubdistrictMojokerto Regency. The method of the research is one group pre test - post test design. The sampling technique used purposive sampling, with the population of hyertension patients in SumberAgung Village JatirejoSubdistrictMojokerto Regency and total of samples is 20 respondents in accordance to the criterias. The data is collected by using ordinal scale and the instrument used is observation paper. It is known from the result of Wilcoxon Signed Ranks Test using SPSS version 16.0 that the value of Ï Value (0,001) < Î±(0,05).It is also obtained that ergonomic exercises has impacts on blood pressure of hypertension patients in SumberAgung Village JatirejoSubdistrictMojokerto Regency. Ergonomic exercises is an effective therapy, easy to do, and beneficial, because ergonomic exercises makes body becomes relax and blood vein becomes vasodilatory which make smooth blood stream and oxygen supply. Keywords : ergonomic exercisers, blood pressure, hypertension